TINGKAT KESEGARAN JASMANI DAN AKTIVITAS FISIK MURID SMP NON- ANEMIA YANG TINGGAL DI WILAYAH KOTA DAN DESA (THE PHYSICAL FITNESS AND ACTIVITIES LEVEL OF NON-ANEMIA SECONDARY SCHOOL STUDENTS IN RURAL AND URBAN AREA) - Yuniar Rosmalina; Dewi Permaesih (Persagi, 2010)
ABSTRACT Background: Adolescence group is considered as human resources potential need to be. Health is main condition to fulfill to succeed the education. Physical fitness is a tool to know the health level. Objective is to determine the physical fitness and physical activities among non anemic adolescence group in rural and urban area. Methods: about 122 respondents non anemic age 11-13 years old from rural and urban area were selected as sample match on according to their age and sex. Data collection including anthropometric measurement (weight, height), fitness was measured by 2.4 km running, sit-ups, sit and reach, muscle strength and body composistion. The fitness level was calculated as average of those 6 components of fitness. Physical activities were collected by 3 days self-report. Results: There is significantly difference found between adolescent in rural and urban area according to the cardiovascular endurance and abdominal strength. The length of physical activities was signifantly difference among rural and urban adolescence. The physical fitness of urban adolescent 46.8 percent were low while in rural only 13.3 percent. Conclusion: The physical fitness of rural non anemic adolescence was better compare to those adolescence who are living in urban area. [Penel Gizi Makan 2010, 33(2): 138-147] Keywords: physical fitness, physical activites and adolescence